Eosinophilic esophagitis in pediatric age, state of the art and review of the literature - Iuliano, Silvia; Minelli, Roberta; Vincenzi, Francesca; Gaiani, Federica; Ruberto, Claudio; Leandro, Gioacchino; Bizzarri, Barbara; Nouvenne, Antonio; Di Mario, Francesco; de’Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2018)
Eosinophilic esophagitis (EoE) is a chronic immune-mediated relapsing disease caused by eosinophilic infiltration of the esophageal mucosa which is normally lacking these cells. EoE belongs to the group of the so called Eosinophilic Gastrointestinal Disorders (EGIDs). From a rare and unusual disease, EoE has become an emerging entity and in recent years its incidence and prevalence have increased all over the world, also in children. The pathogenesis is very complex and still not completely clear. Esophageal disfunction symptoms (e.g. dysphagia and food impaction) represent the typical manifestation of EoE and this condition could be difficult to recognize, more in pediatric age than in adults. Moreover, symptoms can often overlap with those of gastro-esophageal reflux disease (GERD), leading to a delayed diagnosis. EoE is often related to atopy and an allergological evaluation is recommended. Untreated EoE could provoke complications such as strictures, esophageal rings, narrowing of the esophagus. Diagnosis is confirmed by the demonstration in biopsy specimens obtained through upper endoscopy of eosinophilic inflammation (>15 for high powered field) of the esophageal mucosa and other histological features. Other tests could be useful not specifically for the diagnosis, but for the characterization of the subtype of EoE. Since EoE incidence and knowledge about physiopathology and natural history have increased, the goal of the review is to provide some helpful tools for the correct management in pediatric age together with an overview about epidemiology, pathogenesis, clinical, diagnosis and treatment of the disease.